2015
DOI: 10.1080/10962247.2015.1100693
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PM2.5 and PM10 fugitive dust source profiles in the Athabasca Oil Sands Region

Abstract: Several organic compounds typical of combustion emissions and bitumen are enriched relative to forest soils for fugitive dust sources near oil sands operations, consistent with deposition uptake by biomonitors. AOSR dust samples are alkaline, not acidic, indicating that potential acid deposition is neutralized. Chemical abundances are highly variable within emission inventory categories, implying that more specific subcategories can be defined for inventory speciation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 63 publications
(72 reference statements)
1
53
1
Order By: Relevance
“…EC abundances were lowest in NS (0.004% ± 0.009%) while Inorganic ions fraction were most abundant in URD (1.49% ± 1.06%). These results agreed well with studies in other regions of the world [15][16][17]19], and indicated that human activity-related factors, such as vehicle exhaust, can greatly modify the chemical characteristics of entrained crustal material from sources affected by these activities.…”
Section: Contributions Of the Major Componentssupporting
confidence: 81%
“…EC abundances were lowest in NS (0.004% ± 0.009%) while Inorganic ions fraction were most abundant in URD (1.49% ± 1.06%). These results agreed well with studies in other regions of the world [15][16][17]19], and indicated that human activity-related factors, such as vehicle exhaust, can greatly modify the chemical characteristics of entrained crustal material from sources affected by these activities.…”
Section: Contributions Of the Major Componentssupporting
confidence: 81%
“…The TERRA algorithm, aircraft observations of total particulate matter number concentration and size close to the sources, and the fugitive dust speciation reported in Wang et al (2015) were used to estimate fugitive dust emissions for six oil sands facilities, for the 12 particle bin version of the GEM-MACH model (Zhang et al, 2017). We refer to these emissions and corrections to deposition based on them hereafter as "aircraft-observation-based".…”
Section: Estimates Of Primary Particulate Emissions and Resulting Bc mentioning
confidence: 99%
“…That site was excluded from the organic-carbon range discussion in Wang et al (2015) and was excluded here as well.…”
Section: Epa Speciate V43 Database (See Section 3) Wang Et Al (201mentioning
confidence: 99%
“…Their analysis showed that PM speciation is clearly different between the dust collected from the facility sites and from the forest sites. For this study, the new AOSR-15 specific fugitive-dust PM speciation profile was compiled by averaging the site-specific profiles from all 17 facility sites from Wang et al (2015) to represent surface PM speciation with the following three exceptions: 1) For the unpaved-road site S16, the elemental-carbon percentage seemed to be too large, which might be an artefact due to dry deposition from heavy-duty diesel exhaust (Wang et al, 2015). This site was excluded from the facility profile average in their study and was excluded in this study too.…”
Section: Epa Speciate V43 Database (See Section 3) Wang Et Al (201mentioning
confidence: 99%
See 1 more Smart Citation